THE INFLUENCE OF PROFITABILITY, COMPANY SIZE, AND LEVERAGES ON TAX AVOIDANCE - Paraswati, Anggita Widia; Purwaningsih, Eny (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
The research aims to empirically test the influence of profitability, company size, and leverage on tax avoidance. The independent variables are profitability with the Net Profit Margin, firm size with the natural logarithm of total assets, leverage with debt to equity ratio and the dependent variable uses tax avoidance with the Effective Tax Rate minus the Cash Effective Tax Rate. The samples tested in the research were the substance of the property and real estate subsector listed on the IDX for the 2019 to 2021 period. There are financial reports for 17 entities, with 51 data assessed as meeting the criteria. The research method uses descriptive statistical tests, which then perform classical tests of hypotheses, including normality, heteroskedasticity, multicollinearity, and autocorrelation. In addition, the hypothesis regarding the influence of the independent variable on the dependent variable is tested. This test uses F-test statistics (simultaneous), T-test (partial), and coefficient of determination, which are then continued in the study using multiple regression analysis. Based on the subtest results, it was found that profitability and debt have significantly favorable effects on tax avoidance and that firm size has no effect on tax avoidance.